Analisis Kepuasan Konsumen terhadap Produk Serbuk Kedelai Mandala 525 - Tambunan, Pascal Christian Maranatha; Yudha, Eka Purna (Universitas Galuh, 2024)
Seeing from the high demand in Indonesia, soybeans became one of the food crops that entered the food market in Indonesia along with other foods in the government program called Upsus (Special Efforts). Due to the high potential of soybeams in Indonesia. Therefore, this research aims to find out the desires that consumers have so that CV. Ints Natural Garlic can develop their products in the direction desired by their own consumers. The data analysis used in this study uses the Customer Satisfaction Index (CSI) and Importance Performance Analysis methods. (IPA). The results of the research show that the level of consumer satisfaction with mandala 525 soy powder products is still unsatisfied and attributes that need to be improved in order to make consumers feel satisfied with the product are features, durability, reliability, aesthetics, perceived quality, conformance to specification and serviceability.